PENGARUH PELATIHAN DAN PROMOSI TERHADAP PRESTASI KERJA Studi pada Pegawai di Kantor Kecamatan Blimbing Kota Malang: Anna Satriana - ANNA SATRIANA (STIA MALANG, 2019)
Abstract Training and development is defined as the preparation of individuals to assume different or higher responsibilities within the organization. Training and development are typically associated with the necessary emotional and skill upgrading to perform better jobs. Development stands on the fact that an employee will need the knowledge, skills and abilities that develop so that employees can work well in a series of succession positions that will be lived during his career. Providing training to employees can also mean improving employee standards, which indicate an increase in the ability and skills of employees to perform certain jobs or tasks. One of the reasons why companies provide training to employees is to improve employee performance. With the improvement of employee performance is expected to goals and objectives set by the company can continue to run smoothly and in accordance with the set by the management company. A form of motivation that can effectively encourage a person to participate actively in an organization, among others, is the opportunity to feel progress in his work, both in position and authority. The opportunity to move forward is often called promotion. Promotion means trust and acknowledgment of the employee's ability and skills to occupy a higher position. Keywords: Training, Promotion, Job Performance